Breast cancer quantitative proteome and proteogenomic landscape - Henrik J. Johansson; Fabio Socciarelli; Nathaniel M. Vacanti; Mads H. Haugen; Yafeng Zhu; Ioannis Siavelis; Alejandro Fernandez-Woodbridge; Miriam R. Aure; Bengt Sennblad; Mattias Vesterlund; Rui M. Branca; Lukas M. Orre; et al. (Nature Communications, 2019)
Gene expression profiles can classify breast cancer into five clinically relevant subtypes. Here, the authors perform an in-depth quantitative profiling of the proteome of 45 breast tumors, and show they can recapitulate the transcriptome-based classifications and identify many potentially antigenic tumour-specific peptides.